JOB SATISFACTION AS A MEDIATION VARIABLE IN THE RELATIONSHIP BETWEEN WORK SAFETY AND HEALTH (K3) AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE - Gamal, Nadira Laraswati; Taneo, Stefanus Yufra M.; Halim, Lidia (Universitas Brawijaya, Indonesia, 2018)
This research aims to determine the direct and indirect effect of work safety and health (K3) and work environment to employee's performance. The sample for this research is the 86 employees at CV Purindah Lawang Malang. Sampling technique that was used is the census technique. The data was obtained from respondents collecting data tools, which is a questionnaire. Data analysis that was used is path analysis. In this research, there are four variables, which are work safety and health (K3) and work environment as independent variables, employee's performance as a dependent variable, and work satisfaction as a mediator variable. The result of this research proves that work satisfaction is a media to improve the work environment's effect on employee's performance. So, the company should provide earplug, give allowance to the employees, and apply a standardized workspace layout. In conclusion, high work satisfaction is needed by employees in every company.